Perceived acceptance and sense of belonging among LGBTQ college students of Pamantasan ng Lungsod ng Maynila - Cassiopeia C. Valmonte. 4 0 16; 5 (2018)
ABSTRACT: For the past decade, the LGBTQ community has been acknowledge and considered to be a big part of the immensely growing population. At present, prejudice against the LGBTQ community have radically minimized. In the Philippines, a drastic number of citizens tolerate homosexual, bisexual and queer individuals despite the conventional and religious culture. However, lack of acceptance is still a global concern to most LGBTQ youths. This has been problematic among households, friends, and learning institutions. The needs for acceptance and belonging are necessities to the psychological well-being and one's self-image. Issues concerning the mental state of LGBTQ youths must be prioritized and further analysed. Few researches have delved upon these concerns, with that, this study aims to measure levels of perceived acceptance and sense of belonging among LGBTQ college students. Apart from that, the main goal of this study is to determine if there is an existing relationship between perceived acceptance and sense of belonging. Purposive sampling was utilized to obtain 77 self-identified LGBTQ individuals from the university. These individuals were asked to fill out the demographic survey. Subsequently, Perceived Acceptance Scale (IPAS) and Sense of Belonging Instrument-Psychological (SOBI-P) was administered to measure the level of perceived acceptance and sense of belonging respectively. Results show that majority of the respondents are average in terms of their level of perceived acceptance and sense of belonging. Moreover , results indicate a strong positive correlation between perceived acceptance and sense of belonging, rejecting the null hypothesis.
Undergraduate Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2018.
Keywords: 2 -- 0; 6; 20; 20; 2